TRANSLATION OF TEXT IN ENVIRONMENTAL ASPECT OF INTERNATIONAL COMMUNICATION - M Yu Avdonina; N G Valeeva; N I Zhabo; S I Terekhova (RUDN Journal of Ecology and Life Safety, 2016)
Teaching and learning translation of professionally-oriented texts has received a new dimension thanks to ICT. Methodological, didactic and psychological analysis of teacher and students practical activity is proposed in order to achieve the goal to go beyond providing information when interpreting information, to reveal deeper meaning, to identify cultural and pragmatic plans of the text in the course of the analysis before translation of the text on ecology.